Nazwy wyrobów z mąki w mowie mieszkańców dawnych Kresów Południowo‑Wschodnich (na przykładzie kilku wsi z obwodu lwowskiego) - Anna Kostecka-Sadowa (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2023)
The aim of this article is to describe the generational characteristics of flour products in the speech of Poles of the former South‑Eastern borderlands on the example of several villages from the Lviv region. My analyses focus on the dynamics of changes in the functioning of food names. The presented material and its preliminary analyses allow to unambiguously assign many names of dishes to specific generational groups of people studied. Comparison of the discussed names of dishes with the content of SGP showed that many of them are common with Polish dialect in the Poland. Confrontation with the Dictionary of the Ukrainian language and Ukrainian dialectological works from the studied area showed that many words coexist in Ukrainian, for example: buchanka, paska, pampuch, bublik, kałacz, korowaj, zawiwańce, pierożek, blin, palanycia.